Splitting, generation, and annihilation of phase singularities in non-coaxial interference of Bessel–Gaussian beams. (6th September 2021) - Zhang, Yagang; Wu, Zhenkun; Yang, Kaibo; Li, Peng; Wen, Feng; Gu, Yuzong
Abstract: Based on the non-coaxial interference of Bessel–Gaussian (BG) beams, a new complex-structured light field is formed. By varying the off-axis distance, phase difference, separation angle, and topological charges (TCs) of the component beams, we observed the splitting, generation, and annihilation of phase singularities. The net TCs of the composite light field is not always equal the sum of the TCs of the original beams. Different from the general single-ringed vortex beams, because BG beams have infinitely many rings, alternately positive and negative unit vortex chains arise in the interference region. Furthermore, the edge dislocations are unstable, by modulating the phase difference and separation angle, we observe controllable transitions between edge dislocations and vortex singularities. Beyond providing an effective method for studying composite vortex beam interference, our results are significant for laser calibration and complex particle manipulation.